Behaviour therapy for obesity treatment considering approved drug therapy - Kossmann, Beate (German Medical Science GMS Publishing House, 2008)
INTRODUCTION: Obesity is a worldwide health problem whose prevalence is on the increase. Many obesity-associated diseases require intensive medical treatment and are the cause of a large proportion of health-related expenditures in Germany. Treatment of obesity includes nutritional, exercise and behaviour therapy, usually in combination. The goal of behaviour therapy for obesity is to bring about a long-term alteration in the eating and exercise habits of overweight and obese individuals. Under certain circumstances, drug treatment may be indicated. OBJECTIVES: What is the effectiveness of behaviour therapy for obesity considering approved drugs reduce weight under medical, economic, ethical-social and legal aspects? METHODS: A systematic review was conducted using relevant electronic literature databases. Publications chosen according to predefined criteria are evaluated by approved methodical standards of the evidence-based medicine systematically and qualitatively. RESULTS: In total 18 studies, included one HTA and one meta-analysis could be identified according to the predefined inclusion criteria. Three studies compare behaviour therapy to other therapy forms (advice or instruction on nutritional changes, physical activity or a combination of the two), six studies evaluate different forms of behaviour therapy, four studies and four studies compare behaviour therapies mediated by Internet or telephone. Three studies could be identified examining the effect of the combination of behaviour and drug therapy. Furthermore one HTA and one meta-analysis could be included in the evaluation. The behaviour therapy in comparison with other therapy forms reveals a higher effectiveness. In comparison of the different therapeutic approaches of the behaviour therapy intensive behaviour therapy forms and group therapy show a higher effectiveness. Studies related to behaviour therapy based on media support demonstrate a weight reduction both through the interventions of media alone as well as through the intervention of media in conjunction with personal support within the groups. However, analyses of the inter-group comparisons offer no statistically significant difference. However, analyses of the inter-group comparisons offer no statistically significant difference. Comparative analyses confirm the effectiveness of behaviour therapy in combination with additional drug treatment when compared to behaviour therapy alone. In all the studies presented here, relevant changes in weight of -5% to -10% are only partially achieved. High weight losses of less than -10% were found among the intervention group in two of the studies. One study reported a weight loss of -11.4% with the “group therapy” intervention method, while another study reported a weight loss of -11.2% with the “behaviour therapy plus drug treatment” intervention method. Studies with a subsequent follow-up period indicate a clear weight loss at the end of the intervention followed by a renewed weight gain towards the end of the follow-up period. For the evaluation of economic, social-ethical or legal aspects we could not identify any studies. DISCUSSION: A comparative assessment among the studies proved difficult due to their heterogeneous nature. Little conformity can be detected in either the contents of the behaviour therapy or in the treatment plans. The length of the follow-up periods also varies from study to study. Many studies only analyze weight changes within one group or for the entire study population. However, the results of these analyses all indicate a significant weight loss at the end of the intervention. CONCLUSION: Some effects of behaviour therapy on a reduction in weight can be shown. However, relevant weight changes of -5% to -10% are only achieved to a certain extent. The extremely heterogeneous nature of the interventions makes a comparison of the study results very difficult. A trend can be detected indicates that those treatments which offer drug treatment in addition to behaviour therapy are more effective than behaviour therapy alone. For the verification of long-term successes of a behaviour therapy too few data are available.